Impact of Donor Age on Recipient Survival in Adult-to-Adult Living-donor Liver Transplantation. Issue 6 (June 2018) - Kubota, Toyonari; Hata, Koichiro; Sozu, Takashi; Ueda, Yoshihide; Hirao, Hirofumi; Okamura, Yusuke; Tamaki, Ichiro; Yoshikawa, Junichi; Kusakabe, Jiro; Tanaka, Hirokazu; Kageyama, Shoichi; Anazawa, Takayuki; et al.
Abstract : Objective: To investigate the influence of donor age on recipient outcome after living-donor partial liver transplantation (LDLT). Background: Donor age is a well-known prognostic factor in deceased donor liver transplantation; however, its role in LDLT remains unclear. Methods: We retrospectively analyzed 315 consecutive cases of primary adult-to-adult LDLT in our center between April 2006 and March 2014. Recipients were divided into 5 groups according to the donor age: D-20s ( n = 60); D-30s ( n = 72); D-40s ( n = 57); D-50s ( n = 94); and D-60s ( n = 32). The recipient survival and the association with various clinical factors were investigated. Results: Recipient survival proportions were significantly higher in D-20s compared with all the other groups ( P = 0.008, < 0.001, < 0.001, and = 0.006, vs D-30s, -40s, -50s, and -60s, respectively), whereas there was no association between recipient survival and their own age. There are 3 typical relationships between donors and recipients in adult-to-adult LDLT: from child-to-parent, between spouses/siblings, and from parent-to-child . The overall survival in child-to-parent was significantly higher than in spouses/siblings ( P = 0.002) and in parent-to-child ( P = 0.005), despite significantly higher recipient age in child-to-parent [59 (42–69) years, P < 0.001]. Contrastingly, parent-to-child exhibited the lowest survival, despite the youngest recipient age [26 (20–43) years, P < 0.001]. In addition, younger donor age exhibited significantly better recipient survival both in hepatitis C virus-related and in non-hepatitis C virus diseases. Univariate and multivariate analyses both demonstrated that donor age and graft-type (right-sided livers) are independent prognostic factors for recipient survival. Conclusions: Donor age is an independent, strong prognostic factor in adult-to-adult LDLT. Abstract : Supplemental Digital Content is available in the text